2011
DOI: 10.2174/187152611795589663
|View full text |Cite
|
Sign up to set email alerts
|

HIV Treatment Adherence, Drug Resistance, Virologic Failure: Evolving Concepts

Abstract: Poor adherence to combined antiretroviral therapy (cART) has been shown to be a major determinant of virologic failure, emergence of drug resistant virus, disease progression, hospitalizations, mortality, and health care costs. While high adherence levels can be achieved in both resource-rich and resource-limited settings following initiation of cART, long-term adherence remains a challenge regardless of available resources. Barriers to optimal adherence may originate from individual (biological, socio-cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
165
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(173 citation statements)
references
References 73 publications
6
165
0
2
Order By: Relevance
“…2 Many studies have demonstrated that youth living with HIV frequently have poor medication adherence. 3 Several crosssectional studies have described low self-efficacy, depression, poor coping styles, and poor social support as social-cognitive predictors of low adherence.…”
Section: Introductionmentioning
confidence: 99%
“…2 Many studies have demonstrated that youth living with HIV frequently have poor medication adherence. 3 Several crosssectional studies have described low self-efficacy, depression, poor coping styles, and poor social support as social-cognitive predictors of low adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Once explained the common features of the CD4+ T-Helper cells, let's explicate the terms which characterise the dynamics of the naive T lymphocytes (T h ) in Equation (3).…”
Section: The Modelmentioning
confidence: 99%
“…The adverse effects and the complexity of treatment regimens (due to the high number of pills and to dosing frequency) may reduce patient's compliance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Pill counts (Achieng et al 2011) and pharmacy refill monitoring have been shown to be reliable and inexpensive but not consistent across all settings. Directly observed ART has also been examined with mixed results but overall is costly and labor intensive (Nachega et al 2010;Hart et al 2010), as is therapeutic drug monitoring via plasma or hair sampling (van Zyl et al 2011). …”
Section: Sub-saharan Africamentioning
confidence: 99%